Pattern of Ankle Fractures Presenting in the Emergency Department of a Tertiary Care Center- A Descriptive Cross-sectional Study - Timalsina, Prayash; Banskota, Bibek; Chaudhary, Rajesh Kumar; Shrestha, Kiran Pradhan; Regmi, Subhash; Joshi, Amit; Pradhan, Ishor (Nepal Orthopaedic Association Journal, 2025)
BACKGROUNDThis study aims to determine the prevalence of ankle fractures among patients presenting in the emergency department, as well as the injury patterns, demographic profiles, associated injuries, and modes of injury.METHODSThis descriptive cross-sectional study was done at a tertiary care center involving patients presented with ankle fractures at the emergency department between January 1, 2022, and December 31, 2023. All patients diagnosed with ankle fractures were included in the study. Those with missing clinical records or radiographic images presented late (> 2 weeks of injury) and managed in other centers were excluded.RESULTSOut of 2256 patients, 168 (7.45%) had ankle fractures. Among 168 patients, 155 met the inclusion and exclusion criteria. There were 106 (68.39%) males and 49 (31.61%) females, with a mean age of 39.23±18.85 years (range, 6 to 83 years). RTA was seen in 100 (64.5 %) patients. Open fractures were seen in 16 (10.1%) cases. Associated injuries were seen in 53(34.2%) cases.CONCLUSIONAnkle fracture commonly occurs in males in the fourth decade of life. RTA was the most common mechanism of injury. All findings observed were similar to what was reported in international studies.